Systems Virology and Human Cytomegalovirus: Using High Throughput Approaches to Identify Novel Host-Virus Interactions During Lytic Infection - Lee, Chen-Hsuin; Grey, Finn (Frontiers in Cellular and Infection Microbiology, 2020)
Human Cytomegalovirus (HCMV) is a highly prevalent herpesvirus, persistently infecting between 30% and 100% of the population, depending on socio-economic status [1]. HCMV remains an important clinical pathogen accounting for more than 60% of complications associated with solid organ transplant patients [2-4]. It is also the leading cause of infectious congenital birth defects and has been linked to chronic inflammation and immune aging [5-7]. There is currently no effective vaccine and HCMV antivirals have significant side effects. As current antivirals target viral genes, the virus can develop resistance, reducing drug efficacy. There is therefore an urgent need for new antiviral agents that are effective against HCMV, have better toxicity profiles and are less vulnerable to the emergence of resistant strains. Targeting of host factors that are critical to virus replication is a potential strategy for the development of novel antivirals that circumvent the development of viral resistance. Systematic high throughput approaches provide powerful methods for the identification of novel host-virus interactions. As well as contributing to our basic understanding of virus and cell biology, such studies provide potential targets for the development of novel antiviral agents. High-throughput studies, such as RNA sequencing, proteomics, and RNA interference screens, are useful tools to identify HCMV-induced global changes in host mRNA and protein expression levels and host factors important for virus replication. Here, we summarise new findings on HCMV lytic infection from high-throughput studies since 2014 and how screening approaches have evolved.